Nitrogen-doped porous carbon from sucrose-polyaniline precursor co-processing: high CO2 adsorption performance and cyclic stability - Li Zhao; Run Zhang; Yong-sheng Ma; Zhong-hao Wu; Qi Niu; Xin-hua Yuan; Xin-yue Zhou; Kai Li; Qiang Lu (Biomass and Bioenergy, 2027)

Microwave-driven mixed-salt roasting for efficient recovery of lithium and rubidium from lepidolite - Xianlu Yuan; Run Zhang; Xun Ma; Xianzhao Hao; Likang Fu; Yonggang Zuo; Gengwei Zhang; Shixing Wang; Libo Zhang (Journal of Environmental Chemical Engineering, 2026)

The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Chlorine transformation during iron ore sintering co-processing of MSWI fly ash: Phase evolution, metal coupling, and risk-relevant environmental stability - Run Shi; Hao Wang; Congqi Zhang; Rongrong Lei; Hongzhi Ma; Yi Xing; Wei Su; Tingshuang Leng; Yulan Liang (Journal of Hazardous Materials, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Electron transfer rate of pyrogenic carbon in aquatic environments: Establishment of analytical methods, structural drivers, and roles in pollutant degradation - Liang Zeng; Runji Ma; Xiaosong Gu; Jie Ou; Run Zhou; Junjian Wang (Journal of Hazardous Materials, 2026)

Mapping the effectiveness of inter-regional industrial co-processing of municipal incineration fly ash: Evidence from the capital metropolitan area in China - Xinyi Zhang; Run Shi; Fan Fei; Zongguo Wen; Hongzhi Ma; Jiayue Zhang; Liping Zhang (Journal of Environmental Management, 2026)

Biochemical and multi-omics analyses reveal skeletal muscle adaptation to chronic low-salinity stress of marine medaka (Oryzias melastigma) - Tian-Hong Chen; Qing-Hao Zhan; Xiao-Yu Zeng; Ning-Ning Ma; Qi-Liang Li; Run-Jie Jin; Jia-Lang Zheng; Qing-Ling Zhu (Fish Physiology and Biochemistry, 2026)

Impacts of extreme drought events on forest ecosystem resilience in mainland Southeast Asia - Lusha Ma; Kun Yang; Zongqi Peng; Run Sun; Mingfeng Zhang; Danni Su; Jingcong Ma; Yanhui Zhu; Xianchun Pan (Science Bulletin, 2026)

Assessing climate-driven shifts in mariculture across coastal China: Implications for sustainable management and conservation - Yanwei Sun; Ying Li; Run Wang; Xuewei Hou; Renfeng Ma (Regional Studies in Marine Science, 2026)

Extent of soil disturbance and spatial strength degradation induced by spudcan penetration and extraction in clay - Cheng-feng Li; Rui Zhou; Run Liu; Hai-yang Zhang; Peng-cheng Ma (Ocean Engineering, 2026)

ClO₂-induced VBNC state in Enterococcus faecalis poses a health risk in drinking water systems - Ziyi Zhang; Shuai Cheng; Menghua Duan; Yihong Wang; Weipeng Xu; Yiming Lu; Hui Yang; Na Lv; Run Ma; Jiahui Guo; Chao Shi (Journal of Hazardous Materials, 2026)

Enhancing camptothecin biosynthesis in Camptotheca acuminata through CrLAMT transfer from Catharanthus roseus - Ru Huang; Wen-Hui Ma; Bing-Run Yang; Fang Yu; Ping Kou (Biotechnology Letters, 2026)

Co-assembled organic phosphorescent crystals with ultralong phosphorescence in high-temperature and water environment - Bin Li; Ziyi Lu; Wensheng Xu; Run Wang; Jiang Liu; Linshuo Jiang; Yin Xiao; Jianchao Ma; Yang Li; Xilong Yan; Bowei Wang; Ligong Chen (Chemical Engineering Journal, 2026)

CARE: a next-generation high resolution cloud and radiation remote sensing product and its Earth system applications - Husi Letu; Huazhe Shang; Run Ma; Chong Shi; Takashi Y. Nakajima; Hiroshi Ishimoto; Jérôme Riedi; Lesi Wei; Ri Xu; Dabin Ji; Qixiang Sun; Sude Bilige; et al. (Science Bulletin, 2026)

Removal of hexavalent chromium from water using sulfidated nanoscale zero-valent iron: Regeneration and freeze–thaw stability, mechanism, and plant ecotoxicity - Wei Yuzhen; Cheng Aobo; Liu Bei; Ma Jushan; Muhammad Hamdan Rashid; Yu Jialu; Fasih Ullah Haider; Ma Shengyuan; Zhang Qinhu; Chu Run (Journal of Water Process Engineering, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

Research progress on co-processing of MSWI FA using high-temperature industrial waste heat - Hongzhi Ma; Congqi Zhang; Hao Wang; Run Shi; Hao Li; Yan Zhang; Xuguang Wang; Wei Su; Yi Xing; Lei Zheng (Process Safety and Environmental Protection, 2026)

RNA interference with the selenoprotein M gene inhibits the growth promoting effect by selenium supplementation to silkworm Bombyx mori - Run-Hui Ma; Wen-Jie Ge; Fei Hu; Ting-Ting Hong; Kiran Thakur; Shun-Ming Tang; Zhao-Jun. Wei (Journal of Asia-Pacific Entomology, 2026)

Prediction on uplift displacement of tunnel induced by base grouting in soft clay - Jia-run Wu; Yu-liang Lin; Dan He; Ye Ma (Tunnelling and Underground Space Technology, 2026)

Mitigation of adverse effects of calcium on struvite biomineralization for phosphorus recovery - Xingtong Chen; Yongyun Li; Yifei Ma; Bing Li; Yihe Qin; Xiaoman Li; Run Yuan; Jingjing Chen; Suran Huang; Han Li; Haiming Huang (Bioresource Technology, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

The adaptation of prehistoric human activities to environmental changes recorded in a lake core on the Tibetan Plateau - Cunlin Li; Liping Zhu; Qingfeng Ma; Jianting Ju; Marco A. Aquino-López; Qiangqiang Kou; Shuyu Pang; Run Zhang; Minghui Li; Xinmiao Lü; Junbo Wang (Global and Planetary Change, 2026)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Histological and molecular analysis of selenium synergistic RNAi of Dynamin gene in Bombyx mori - Run-Hui Ma; Ting-Ting Hong; Fei Hu; Kiran Thakur; Zhao-Jun Wei (Journal of Asia-Pacific Entomology, 2025)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

Global synthesis of nitrogen management in sugarcane systems: Decoding climate-soil-management drivers of Brazil-China contrasts - Xiaomai Yuan; Shengsen Zhou; Fumin Wei; Li Ma; Yongfeng Sun; Dingjiao Peng; Run Liang; Yibao Luo; Baoshan Chen; Wei Yao; Ziting Wang (Field Crops Research, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

Two-step fabrication of perovskite films with controlled crystal orientation via PbI₂ modulation for high-performance solar cells - Yixuan Wang; Shuheng Jiang; Mengjin Zhang; Zequn Ma; Huishu Li; Run Zhao; Hao Lu (Chemical Engineering Journal, 2025)

A portable slide based MIPs-FL sensor was fabricated for potential on-site detection - Run-tian Ma; Jun Zhang; Jin-xiu Guo; Fang Nian; Cheng Wang; Wei-bing Xu (Food Chemistry, 2025)

Factors contributing to high oxidative stability in oil from long-term stored tiger nut (Cyperus esculentus L.): Endogenous components - Jia-Ke Li; Deng-Ju Cai; Hang-Yu Zhao; Yu-Xiang Ma; Xiao-Shuang Cai; Hua-Min Liu; Run-Yang Zhang (Journal of Stored Products Research, 2025)

Decabromodiphenyl ethane induces intrauterine growth restriction by suppressing placental angiogenesis via TWIST2/NAT10-mediated ac4C-dependent TGF-β1 mRNA stabilization - Run Ling; Xin Yin; Liyao Ma; Yan Zhang; Yidan Ma; Rufei Gao; Yanqing Geng; Xinyi Mu; Xuemei Chen; Fangfang Li; Junlin He (Journal of Hazardous Materials, 2025)

Urban-industrial synergies in Sustainability: Evaluating the Co-processing of MSWI fly ash in industrial kilns from environmental and economic perspectives - Run Shi; Fan Fei; Xuguang Wang; Dawei Liu; Shuang Wu; Junwei Bai; Yan Zhang; Wei Su; Rongrong Lei; Hao Wang; Hongzhi Ma (Journal of Cleaner Production, 2025)

Post-dynamic behaviors of the saturated loess in the Zhongchuan slide triggered by the Jishishan M6.2 earthquake - Haiping Ma; Keliang Ren; Wenguo Ma; Youzhen Yang; Chen Li; Run Cai (Natural Hazards, 2025)

A review of pharmacological effects and bioactive constituents of Euonymus alatus - Na Sun; Yujing Wang; Caihong Zhou; Huanhuan Kang; Run Wang; Xiu Feng; Shuo Ma; Linxuan Jin; Xin Zhang; Penghua Shu (Phytochemistry Letters, 2025)

Laminaria Japonica hydrolysate as a novel biostimulant for enhancing DHA accumulation in Aurantiochytrium limacinum - Jia-Xue Lin; Ying Wang; Shao-Geng Zhao; Bei-Chen Huang; Yue Zhang; Zhi-Qiang Wang; Sheng-Jie Li; Qian Liu; Yan Ma; Jing-Run Ye; Hai-Ying Wang; Zhi-Peng Wang (World Journal of Microbiology and Biotechnology, 2025)

Vortex-Induced Vibration Analysis of FRP Composite Risers Using Multivariate Nonlinear Regression - Lin Zhang; Chunguang Wang; Wentao He; Keshun Ma; Run Zheng; Chiemela Victor Amaechi; Zhenyang Zhang (Journal of Marine Science and Engineering, 2025)
Marine risers are essential for offshore resource extraction, yet traditional metal risers encounter limitations in deep-sea applications due to their substantial weight. Fiber-reinforced polymer (FRP) composites offer a promising alternative with advantages including low density and enhanced corrosion/fatigue resistance. However, FRP risers remain susceptible to fatigue damage from vortex-induced vibration (VIV). Therefore, this study investigated VIV behavior of FRP composite risers considering the coupled effect of tensile-flexural moduli, top tensions, slenderness ratios, and flow velocities. Through an orthogonal experimental design, eighteen cases were analyzed using multivariate nonlinear fitting. Results indicated that FRP composite risers exhibited larger vibration amplitudes than metal counterparts, with amplitudes increasing to both riser length and flow velocity. It was also found that the optimized FRP configuration demonstrated enhanced fiber strength utilization. Parameter coupling analysis revealed that the multivariate nonlinear fitting model achieved sufficient accuracy when incorporating two coupled parameters, with the most significant interaction occurring between flexural modulus and top tension.

Effects of periodic starvation on the characteristics and microbial communities of anammox sludge - Yufeng Zheng; Liangliang Shi; Run Su; Wenhui Min; Yan Wei; Bin Ma (Journal of Environmental Chemical Engineering, 2025)

Restoration of secondary forest in the Greater Mekong Subregion struggles to offset primary forest carbon losses - Zongqi Peng; Yanhui Zhu; Kun Yang; Yi Luo; Xixi Lu; Jiasheng Wang; Yang Zhang; Danni Su; Run Sun; Mingfeng Zhang; Jingcong Ma; Yang Liu; et al. (Global and Planetary Change, 2025)

Comammox and AOA responses to ammonia loading rate in oligotrophic environments - Run Su; Litong Shi; Yan Wei; Bin Ma (Water Research, 2025)

Co species modulating of BiOBr-based Z-scheme heterojunction for the transform photoreduction CO2 products from CO to CH4 - Run-Jing You; Kuan Wang; Huan Ma; Xin-Peng Li; Zhe Cao; Zhen-Hong He; Huan Wang; Weitao Wang; Xiaojuan Lai; Zhao-Tie Liu (Chemical Engineering Journal, 2025)

Remote sensing of liquid cloud profiles based on an analytical cloud profiling model - Huazhe Shang; Husi Letu; Lesi Wei; Run Ma; Yutong Wang; Zhaoxin Cai; Shuai Yin; Chong Shi (Science China Earth Sciences, 2025)

Endophytes and soil microorganisms participate in the germination of Sinojackia xylocarpa Hu by degrading the pericarp - Zi-Hao Li; Xin-Yi Ma; Huan Yang; Run-Guo Zang; Jia-Ru Li (Acta Physiologiae Plantarum, 2025)

Development of a hybrid algorithm for the simultaneous retrieval of aerosol optical thickness and fine-mode fraction from multispectral satellite observation combining radiative transfer and transfer learning approaches - Chenqian Tang; Chong Shi; Husi Letu; Shuai Yin; Teruyuki Nakajima; Miho Sekiguchi; Jian Xu; Mengjie Zhao; Run Ma; Wenwu Wang (Remote Sensing of Environment, 2025)

Neferine induces apoptosis and inhibits metastasis in human endometrial cancer cells by down-regulating miR-1266–5p - Fei-Fei Ma; Run-Hui Ma; Wang-Wei Zhang; Xiu-Xiu Zhang; Qian Zhong; Kiran Thakur; Jian-Guo Zhang; Jesus Simal-Gandara; Hui Cao (Food Bioscience, 2025)

Layer-by-layer nanoencapsulation strategies for enhanced oral delivery and function of Lactobacillus plantarum B2 - Yun-Yang Zhu; Run-Hui Ma; Kiran Thakur; Wang-Wei Zhang; Jian-Guo Zhang; Mohammad Rizwan Khan; Chenzhong Liao; Zhao-Jun Wei (Food Hydrocolloids, 2025)

Paleoproterozoic granite in the Khondalite Belt, northern margin of the North China Craton: Response to the assembly of the Columbia supercontinent - Qiang Shi; Run-Xiao Shu; Xiang-Zhi Chen; Guo-Chun Zhao; Yu-Song Chen; Zhao-Sheng Wang; Long Ma; Zhong-Yuan Xu; Zheng-Hong Liu; Kai-Yun Chen; Hui-Chu Wang (Precambrian Research, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

A domain-decomposition-based parallel approach for 3D geological modeling using radial basis functions interpolation on GPUs - Hong Li; Huizhu Ni; Jinming Fu; Bo Wan; Deping Chu; Fang Fang; Run Wang; Guoxi Ma; Xin Zhou (Earth Science Informatics, 2025)

In-situ and experimental investigations of the failure characteristics of surrounding rock through granites with biotite interlayers in a tunnel - Wei Zhang; Lei Hu; Zhi-Bin Yao; Yong-Run Xiong; Jun Zhao; Tao Ma; Song Chen; Zhe Xu (Engineering Geology, 2024)

Relationship between human activities and environmental changes in the southern Tibetan Plateau since the Little Ice Age - Cunlin Li; Liping Zhu; Qingfeng Ma; Jianting Ju; Jiuju Cheng; Marco A. Aquino-López; Run Zhang; Qiangqiang Kou; Xinmiao Lü; Junbo Wang (Science of The Total Environment, 2024)

Recent advances in soot formation mechanisms: Oxidation and oxidation-induced fragmentation - Huaqiang Chu; Run Hong; Wenlong Dong; Hanfang Zhang; Xiaoyan Ma; Longfei Chen (Fuel, 2024)

Microplastic-free, single-layered functional surface with localized liquid-discharging molecular channels for disposable hygiene products - Mei Liu; Ruimin Xie; Chi Ma; Jielin Xu; Run Zhao; Lili Deng; Shiyan Chen; Jianping Yang; Liming Zou; Huaping Wang; Jing Wu (Chemical Engineering Journal, 2024)

Integrated framework for geological modeling: integration of data, knowledge, and methods - Hong Li; Bo Wan; Deping Chu; Run Wang; Guoxi Ma; Chuanyang Lei; Shengyong Pan (Bulletin of Engineering Geology and the Environment, 2024)

Comparing combined application of biochar and nitrogen fertilizer in paddy and upland soils: Processes, enhancement strategies, and agricultural implications - Xiaomai Yuan; Xiaoyan Gu; Run Liang; Guichen Ban; Li Ma; Tieguang He; Ziting Wang (Science of The Total Environment, 2024)

Overall and geographic pattern of incidence, fatality and mortality of sepsis among hospitalized non-child cancer patients in China: A nationwide cross-sectional study - Bin Lu; Yang Xu; Na Li; Yueyang Zhou; Xudong Ma; Yan Chen; Run Dong; Xiang Zhou; Min Dai; Hongda Chen; Li Weng; Bin Du (Science Bulletin, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Cannabidiol regulates the activation of hepatic stellate cells by modulating the NOX4 and NF-κB pathways - Na Xie; Run Ma; Lian Wang; Yuanhui Shu; Ping He; Yan Zhou; Yining Xiang; Yuping Wang (Food and Chemical Toxicology, 2024)

Long-term exposure to reduced specific-size ambient particulate matter and progression of arterial stiffness among Chinese adults - Dankang Li; Shouling Wu; Linxi Tang; Shuohua Chen; Feipeng Cui; Yudiyang Ma; Run Liu; Jianing Wang; Yaohua Tian (Journal of Hazardous Materials, 2024)

Effects of ammonia addition on soot formation in hydrocarbon fuels combustion: Challenges and prospects - Huaqiang Chu; Shunjie Feng; Run Hong; Xiaoyan Ma; Fen Qiao; Longfei Chen (Fuel, 2024)

Residential greenness and incident idiopathic pulmonary fibrosis: A prospective study - Linxi Tang; Feipeng Cui; Yudiyang Ma; Dankang Li; Jianing Wang; Run Liu; Yaohua Tian (Environmental Research, 2024)

Response of grassland growing season length to extreme climatic events on the Qinghai-Tibetan Plateau - Run Zhong; Kai Yan; Si Gao; Kai Yang; Shuang Zhao; Xuanlong Ma; Peng Zhu; Lei Fan; Gaofei Yin (Science of The Total Environment, 2024)

Plasma-assisted assembly of Co3O4/TiO2-NRs for photoelectrocatalytic degradation of bisphenol A in solution and muddy systems - Xinwei Chen; Hao Ma; Run Wang; Man Wang; Binbin Zhu; Yanqing Cong; Xiayue Zhu; Guoqin Wang; Yi Zhang (Environmental Pollution, 2024)

Lycium barbarum (Goji) as functional food: a review of its nutrition, phytochemical structure, biological features, and food industry prospects - Run-Hui Ma; Xiu-Xiu Zhang; Zhi-Jing Ni; Kiran Thakur; Wei Wang; Ya-Mei Yan; You-Long Cao; Jian-Guo Zhang; Kannan R. R. Rengasamy; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2023)

A predictive model for determining the nitrite concentration in the effluent of an anammox reactor using ensemble regression tree algorithm - Yikun Huang; Run Su; Yinan Bu; Bin Ma (Chemosphere, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Integrating NLP and Ontology Matching into a Unified System for Automated Information Extraction from Geological Hazard Reports - Qinjun Qiu; Zhen Huang; Dexin Xu; Kai Ma; Liufeng Tao; Run Wang; Jianguo Chen; Zhong Xie; Yongsheng Pan (Journal of Earth Science, 2023)

The Experimental Study of Dynamic Response of Marine Riser under Coupling Effect of Multiparameter - Run Zheng; Chunguang Wang; Wentao He; Zhenyang Zhang; Keshun Ma; Mengqi Ren (Journal of Marine Science and Engineering, 2023)
In order to investigate the dynamic response of a marine riser under the coupling effect of multiparameter, a model experiment of a marine riser was designed and carried out. The main parameters of the model test were divided into riser design parameters and flow field parameters. The riser parameters included the elastic modulus, boundary conditions, and top tension forces, and the flow field parameters were the velocities and wave parameters (wave height and period). The riser materials were aluminum (Al) and polymethyl methacrylate (PMMA), representing the metal riser and fiber-reinforced composite marine riser, respectively, which differ greatly in modulus. Two types of boundary conditions were considered, which were simple supports at both ends (S-S) and simple and fixed supports at each end (S-F). The top tension forces were chosen as 10 N and 30 N, respectively. In terms of the flow velocities, 0.3 m/s and 0.7 m/s were used. For the wave types, the small wave had a period of 1.0 s and a wave height of 5 cm while the large wave had a period of 2.0 s and a wave height of 15 cm. The dynamic response of the riser under 32 different working conditions was studied experimentally, and through the analysis of the experimental data, the effects of various parameters on the dynamic response of the risers were obtained. The results show that the amplitude of the riser was negatively correlated with the elastic modulus, the number of constraints, and the magnitude of the top tension, while it was positively correlated with the flow velocity and wave size. Moreover, the sequences of importance were b3 (flow velocity) > b6 (modulus) > b1 (number of constraints) > b2 (top tension force) > b5 (wave height) > b4 (wave period) for the vibration of the riser in the in-flow direction and b3 (flow velocity) > b1 (number of constraints) > b6 (modulus) > b2 (top tension force) > b5 (wave height) > b4 (wave period) for the vibration of the riser in the cross-flow direction, respectively, according to the multiple linear regression calculation.

Evaluation and uncertainty analysis of Himawari-8 hourly aerosol product version 3.1 and its influence on surface solar radiation before and during the COVID-19 outbreak - Chenqian Tang; Chong Shi; Husi Letu; Run Ma; Mayumi Yoshida; Maki Kikuchi; Jian Xu; Nan Li; Mengjie Zhao; Liangfu Chen; Guangyu Shi (Science of The Total Environment, 2023)

Evaluating the saturation effect of vegetation indices in forests using 3D radiative transfer simulations and satellite observations - Si Gao; Run Zhong; Kai Yan; Xuanlong Ma; Xinkun Chen; Jiabin Pu; Sicong Gao; Jianbo Qi; Gaofei Yin; Ranga B. Myneni (Remote Sensing of Environment, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Evolutionary research trend of Polygonatum species: a comprehensive account of their transformation from traditional medicines to functional foods - Xiao-Li Li; Run-Hui Ma; Fan Zhang; Zhi-Jing Ni; Kiran Thakur; Shaoyun Wang; Jian-Guo Zhang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2023)

A novel method for immobilizing anammox bacteria in polyurethane foam carriers through dewatering - Yufeng Zheng; Yuying Zhao; Run Su; Ni An; Youliang Zhang; Yan Wei; Bin Ma (Journal of Water Process Engineering, 2023)

Structural characterization and stability of glycated bovine serum albumin-kaempferol nanocomplexes - Run-Hui Ma; Wei Wang; Cai-Ping Hou; Yi-Fei Man; Zhi-Jing Ni; Kiran Thakur; Jian-Guo Zhang; Zhao-Jun Wei (Food Chemistry, 2023)

Deficiency of Lactoferrin aggravates lipopolysaccharide-induced acute inflammation via recruitment macrophage in mice - Can Liu; Qiu Peng; Lingyu Wei; Zhengshuo Li; Xiaoyue Zhang; Yangge Wu; Jia Wang; Xiang Zheng; Yuqing Wen; Run Zheng; Qun Yan; Qiurong Ye; et al. (BioMetals, 2023)

Retrieval of cloud microphysical properties from Himawari-8/AHI infrared channels and its application in surface shortwave downward radiation estimation in the sun glint region - Gegen Tana; Xu Ri; Chong Shi; Run Ma; Husi Letu; Jian Xu; Jiancheng Shi (Remote Sensing of Environment, 2023)

Genome-wide characterization of LBD transcription factors in switchgrass (Panicum virgatum L.) and the involvement of PvLBD12 in salt tolerance - Cong Guan; Bo Wu; Shu Ma; Jinhong Zhang; Xuesi Liu; Hui Wang; Jinglei Zhang; Run Gao; Huixin Jiang; Chunlin Jia (Plant Cell Reports, 2023)

Liraglutide inhibits AngII-induced cardiac fibroblast proliferation and ECM deposition through regulating miR-21/PTEN/PI3K pathway - Jun Wang; Run Guo; Xiaoli Ma; Ying Wang; Qianyu Zhang; Nan Zheng; Jun Zhang; Chenchen Li (Cell and Tissue Banking, 2023)

Simultaneous regulation of Li-ion intercalation and oxygen termination decoration on Ti3C2Tx MXene toward enhanced oxygen electrocatalysis for Li-O2 batteries - Shidong Song; Fangfang Yin; Yue Fu; Jiahao Ren; Junjie Ma; Yanan Liu; Run Ma; Wanyu Ye (Chemical Engineering Journal, 2023)

Age and fluid source of the sub-volcanic Zhaiping Ag–Pb–Zn deposit in the eastern Cathaysia Block (Fujian Province, Southeastern China) - Ying Ma; Shao-Yong Jiang; Hartwig E. Frimmel; Rui-Chun Duan; Lü-Yun Zhu; Run-Sheng Chen (Mineralium Deposita, 2022)

Genesis of the Hebaoshan gold deposit in Fujian Province of Southeast China: constraints from a combined fluid inclusion, H-O-C-S-Pb-He-Ar isotope and geochronological study - Ying Ma; Shao-Yong Jiang; Hartwig E. Frimmel; Lü-Yun Zhu; Suo-Fei Xiong; Run-Sheng Chen; Xue-Xie Li (Mineralium Deposita, 2022)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

210Po/210Pb Disequilibria in the Eastern Tropical North Pacific - Qiang Ma; Yusheng Qiu; Run Zhang; E Lv; Yipu Huang; Min Chen (Frontiers in Marine Science, 2021)
The 210 Po/ 210 Pb disequilibrium was attempted to reveal the small-scale particle dynamics in the eastern tropical North Pacific. Seawater samples in the full water column were collected from three sites in the Tehuantepec bowl near the East Pacific Ridge for determination of dissolved and particulate 210 Po and 210 Pb. Our results show that TPo/TPb activity ratios in the full water column at the three sites are less than 1, with an average of 0.56, indicating that the total 210 Po in the oligotrophic sea is significantly deficient. The activity ratios of DPo/DPb in the dissolved phase are less than 1, while those in the particulate phase are greater than 1 (except for the bottom 300 m), indicating fractionation between 210 Po and 210 Pb in the scavenging process. A negative linear relationship between 210 Po deficit and silicate proves that biological activities are responsible for 210 Po deficiency in the upper 200 m. However, the deficit of 210 Po in the bottom 300 m may be caused by the horizontal transport of the hydrothermal plume. After correcting the horizontal contribution, the removal rates of 210 Po for the 200–1,500 m and the bottom 300 m layers increased by 7.5–21 and 26.1–29.5%, respectively. Correspondingly, the variation range of the residence time of a total 210 Po became smaller. Our calculations suggest that horizontal transport is acting as a stabilizer for small-scale variation in the 210 Po deficit in the eastern tropical North Pacific. Our study highlights the need to pay more attention to the small-scale variation of 210 Po deficit when applying 210 Po/ 210 Pb disequilibria to trace biogeochemical processes, and the mechanism responsible for this variation deserves further study.

Landslide mapping and analysis along the China-Pakistan Karakoram Highway based on SBAS-InSAR detection in 2017 - Xiao-jun Su; Yi Zhang; Xing-min Meng; Dong-xia Yue; Jin-hui Ma; Fu-yun Guo; Zi-qiang Zhou; Mohib Ur Rehman; Zainab Khalid; Guan Chen; Run-qiang Zeng; Fu-meng Zhao (Journal of Mountain Science, 2021)

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Numerical modeling of the 2008 Wenchuan earthquake-triggered Niumiangou landslide considering effects of pore-water pressure - Da Huang; Yi Xiang Song; Guo Wei Ma; Xiang Jun Pei; Run Qiu Huang (Bulletin of Engineering Geology and the Environment, 2019)

Nitrogen uptake regime regulated by ice melting during austral summer in the Prydz Bay, Antarctica - Run Zhang; Qiang Ma; Min Chen; Minfang Zheng; Jianping Cao; Yusheng Qiu (Acta Oceanologica Sinica, 2019)

Prepulse Inhibition of Auditory Cortical Responses in the Caudolateral Superior Temporal Gyrus in Macaca mulatta - Zuyue Chen; Lauri Parkkonen; Jingkuan Wei; Jin-Run Dong; Yuanye Ma; Synnöve Carlson (Neuroscience Bulletin, 2018)

Increasing the yield of middle silk gland expression system through transgenic knock-down of endogenous sericin-1 - Sanyuan Ma; Xiaojuan Xia; Yufeng Li; Le Sun; Yue Liu; Yuanyuan Liu; Xiaogang Wang; Run Shi; Jiasong Chang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2017)

Inhibitory effect of estrogen receptor beta on P2X3 receptors during inflammation in rats - Qian Jiang; Wen-xin Li; Jia-run Sun; Tian-tian Zhu; Juan Fan; Li-hua Yu; Geoffrey Burnstock; Hua Yang; Bei Ma (Purinergic Signalling, 2017)

Insights into the coupling of upper ocean-benthic carbon dynamics in the western Arctic Ocean from an isotopic (13C, 234Th) perspective - Run Zhang; Min Chen; Qiang Ma; Jianping Cao; Yusheng Qiu (Acta Oceanologica Sinica, 2015)

Expression profiles of miRNAs in Gossypium raimondii - Jun Ma; Teng-long Guo; Qing-lian Wang; Kun-bo Wang; Run-run Sun; Bao-hong Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

Latitudinal distribution of nitrogen isotopic composition in suspended particulate organic matter in tropical/subtropical seas - Run Zhang; Min Chen; Qiang Ma; Jianping Cao; Yusheng Qiu (Isotopes in Environmental and Health Studies, 2011)

Repair of glutamate-induced excitotoxic neuronal damage mediated by intracerebroventricular transplantation of neural stem cells in adult mice - Juan Ma; Li-Jian Yu; Run-Di Ma; Yong-Ping Zhang; Juan-Zhi Fang; Xiao-Yu Zhang; Ting-Xi Yu (Neuroscience Bulletin, 2007)